The Competitivenes of Wood Processing Industry in the Republic of Serbia During The Period 1995-2015 - Milićević, Srđan; Nikolić, Miroljub; Cvetanović, Slobodan (Industrija, 2017)
The paper considers the competitiveness of wood processing industry in the Republic of Serbia in the period 1995-2015 by using six partial indicators of competitiveness: Revealed comparative advantage (RCA), Competitiveness growth index (RCA1), Index of net business performance (RCA2), Index of contribution to the trade balance (CTB), Grubel-Lloyd index (GLI) and Michaely index (MI). The research reveals that the values of RCA were positive in all years, which points to comparative advantage of wood processing industry on the domestic market. Since RCA1 has significantly higher value than one, it means that it is highly competitive on international market as well. Positive values of RCA2 in the period 1995-2015 speak of the contribution of this branch to international economic balance. The indicator RCA2 is connected with the CTB index, which points to the contribution of the sector in formation of active national trade balance and economic growth. The average value of CTB index of wood processing industry in Serbia and positive annual values of CTB of wood processing industry show that the contribution in the total trade balance of the sector is positive. The course of GLI values points to the loss of capabilities of the sector to create the surplus of national trade balance. Finally, positive annual values of MI confirmed the competitiveness of domestic wood processing industry, but at the same time its low specialisation. Taken as a whole, the weakness of competitiveness of wood processing industry in Serbia can be seen in the fact that its competitive advantage is visible in its favourable price, not in manufacturing complex products with high value added. The aim of the paper is to investigate whether Serbian wood processing industry has comparative precedence on domestic and international markets and whether the structure of exchange is positive, i.e. whether appropriate specialisation of production and export exists or the focus should shift onto more complex products and value added.